2015
DOI: 10.18632/oncotarget.4377
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid dampens oncogenic apoptosis induced by endoplasmic reticulum stress during hepatocarcinogen exposure

Abstract: Hepatocellular carcinoma (HCC) is characterized by the accumulation of unfolded proteins in the endoplasmic reticulum (ER), which activates the unfolded protein response (UPR). However, the role of ER stress in tumor initiation and progression is controversial. To determine the impact of ER stress, we applied tauroursodeoxycholic acid (TUDCA), a bile acid with chaperone properties. The effects of TUDCA were assessed using a diethylnitrosamine-induced mouse HCC model in preventive and therapeutic settings. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…It is reported that TUDCA reduces ER stress through binding to the hydrophobic regions of proteins, and promoting the protein folding and aggregation. 44,45) This result indicated that bavachin-induced apoptosis was associated with ER stress pathways.…”
Section: Discussionmentioning
confidence: 84%
“…It is reported that TUDCA reduces ER stress through binding to the hydrophobic regions of proteins, and promoting the protein folding and aggregation. 44,45) This result indicated that bavachin-induced apoptosis was associated with ER stress pathways.…”
Section: Discussionmentioning
confidence: 84%
“…UPR is an important tightly regulated response required for cellular homeostasis, and it intersects with many other pathways that are critical for glucose metabolism, glycogen synthesis, lipid metabolism, inflammation, and metabolic disease 45. Recent studies have shown that the UPR plays a role in liver disease,46, 47 that its activation is associated with hepatic insulin resistance and fatty acid flux,48, 49 and that the UPR mediator XBP1 can up‐regulate hepatic lipogenic factor 47, 50. Our study suggests that overexpression of MAN1A1 leads to steatosis, inflammation, and HCC formation, possibly through the UPR, perhaps evoking the transcriptional networks involved in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we are interested in tauroursodeoxycholic acid (TUDCA), a safe hydrophilic bile acid that is known for its ER stress-reducing capacities in hepatic and non-hepatic cells in vitro and in vivo. [20][21][22][23][24][25][26][27][28][29][30][31][32] TUDCA has recently been shown to bind to the hydrophobic regions of proteins, acting as a chemical chaperone, preventing subsequent protein aggregation and unfolded protein accumulation, thus diminishing ER stress. 33 In this study, we investigated the mode of cell death and UPR activation following experimental APAP overdose in mice and whether modulating these processes by TUDCA might provide an additional therapeutic effect to the standard of care treatment with NAC.…”
Section: Introductionmentioning
confidence: 99%